Developing Reading Comprehension among Students through Metacognitive Instructional Strategy - Noor, Misbah; Siddiqui, Ghazal Khalid; Khan, Ayaz Muhammad (Annals of Human and Social Sciences, 2023)
This research conducted to explore the metacognitive instructional strategy of self assessment effect on student’s reading comprehension in a public school of Punjab in the context of Pakistan. The objective of the current study was to find out; the effect of metacognitive self-assessment strategy on student’s reading comprehension at 7th grade. The current study used experimental design that involves the two groups (experimental and control groups) pre-test and post-test was adopted. The experimental group treatment was given by self-assessment metacognitive strategy and control group was used the traditional lecture method. The sample consisted of 58 students of a public girls’ high school. Reading comprehension test for data collection was developed by the researcher and Mean, standard deviation, t-test were used for analysis. Results indicated that those students given the treatment attained higher scores compared to control group students. So, it is suggested that metacognitive instructional strategy should be adopted by instructors on a regular basis in their English language classroom.